TEACHERS OF 21ST CENTURY: TEACHERS’ ROLES IN INNOVATING LEARNING STRATEGIES AND CHALLENGES - Wayan Maba,; Ida Bagus Nyoman Mantra,; Ida Ayu Made Sri Widiastuti, (International Journal of Social Science, 2023)
One of the indicators of teacher professional competence is being able to utilize technology in the learning process to answer the challenges of the times. This is in accordance with the competence of 21st-century teachers, namely having good skills and digital literacy. In other words, teachers' competence from time to time must continuously be upgraded to keep up with the development. This study used qualitative research design to investigate the teachers’ roles in innovating learning strategies. The study found that teachers are required to use various skills in developing teaching and learning strategies to meet the demand of the students to equip them with sufficient knowledge and skills to survive in this new millennium era. Furthermore, this study highlights that teachers should continually upgrade their knowledge and ability to conduct learning activities professionally